Tecnología para el uso de explosivos - Cuellar Borja, Raúl (My University, 2000)
According to Persson. Steady state detonation along a cylindrical charge can be regarded as a self propagating process in which the axial compressive effect of the shock front discontinuity changes the state of the explosive so that exothermic reaction sets in with the requisite velocity.
Keywords: Cylindrical; explosives; velocity; function; laboratory